A pertinência temática e o controle concentrado de constitucionalidade: o interesse de agir à luz do papel do Supremo Tribunal Federal como guardião da Constituição - Vainer, Bruno Zilberman (2009)
This Masters thesis is intended to review the so-called pertinência temática [subject matter pertinence, as a free translation], a specific legal-interest demonstration requirement introduced by the Federal Supreme Court, and which it imposed on some of the entities that have jurisdiction to enforce concentrate constitutional control. Indeed, the aforesaid requirement actually limits concentrate constitutional control, insofar as the Federal Supreme Court thus avoids review of relevant constitutional matters, simply by denying further processing to actions on grounds of lack of legal interest to sue.The subject-matter requirement becomes all the more deleterious when it reaches strict actions involving concentrate control, where, typically, there are neither parties nor a claim of one s interest, and where there is no litigation in the strict sense of the term. As a matter of fact, the subject matter of such actions is but the in abstracto determination of constitutional grounds of a given rule, with a view at safeguarding the system from rules that might otherwise violate the Federal Constitution. To that effect, this work begins with a brief introduction that deals with the main issues and features of concentrate control and reviews base-control systems (of the USA, Austria and France) with particular emphasis on their influence on the Brazilian Law. Likewise, this work provides a summarized background on constitutional control in Brazil and a critical discussion on each appropriate entity, particularly in the light of the Federal Supreme Court case law and best-reputed collection of legal studies. This work is completed with some recommendations intended to change the current scenario, such as to lessen access-limitation to the entities that have jurisdiction to enforce concentrate constitutional control and to assure that the Federal Supreme Court s highest purpose to safeguard the Constitution is attained in an effective manner